Model Kepemimpinan Transformasional dalam Dunia Pendidikan di Era Digital - Akhmad Makmur; Muhammad Aep Saepudin; Tanto Sudarto; Ahmad Maftuh; Purwadi Purwadi (Syntax Corporation Indonesia, 2023)
....